Frakcjonowanie metali ciężkich w osadach ściekowych ustabilizowanych beztlenowo = Fractionation of heavy metals in sewage sludge after digestion - Dąbrowska, Lidia (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The speciation analysis of heavy metals in biochemically stabilized sewage sludge gives information important for determination of the rate at which heavy metals pass into soil solution and also, as a consequence, their uptake by plants. This information is especially important when considering agricultural usage of sludge.
Keywords: metale ciężkie; frakcjonowanie; mobilność; osady ściekowe; heavy metals; fractionation; mobility; sewage sludge; digestion